REINSTATEMENT OF BEGONIA LEPIDA BLUME - Deden Girmansyah (Floribunda, 2012)
Based on a morphological characters analysis, the typical individuals of B. lepida and B. bracteata are easily distinguished. Consequently, B. lepida is reinstated as species level.